Stella by starlight - Draper, Sharon M. (Sharon Mills) (Atheneum Books for Young Readers, 2015)
When a burning cross set by the Klan causes panic and fear in 1932 Bumblebee, North Carolina, fifth-grader Stella must face prejudice and find the strength to demand change in her segregated town.